2005
DOI: 10.1136/hrt.2004.047068
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of poor mid-term health related quality of life after primary isolated coronary artery bypass grafting surgery

Abstract: Objective: To assess the determinants of poor mid-term health related quality of life (HRQoL) at one year after primary isolated coronary artery bypass grafting (CABG). Methods: 463 patients who underwent primary isolated CABG for multivessel disease and came for their annual follow up at the outpatient clinic during one year at Harefield Hospital, Middlesex, were approached to participate in the present study. Prospective clinical data were collected as part of the clinical care of the patients and were retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 30 publications
5
78
2
1
Order By: Relevance
“…The findings of the current study are in line with previous studies in patients with peripheral arterial disease [13], treated with revascularization procedures [16,35], and patients with chronic heart failure [14], showing that Type D patients report poorer health status compared to non-Type D patients despite both personality taxonomies benefiting from medical treatment. In the present study, we found a non-significant interaction effect for Type D personality by time, indicating that personality did not moderate the effects of cardiac rehabilitation on health status but exerted a stable effect on health status over time.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of the current study are in line with previous studies in patients with peripheral arterial disease [13], treated with revascularization procedures [16,35], and patients with chronic heart failure [14], showing that Type D patients report poorer health status compared to non-Type D patients despite both personality taxonomies benefiting from medical treatment. In the present study, we found a non-significant interaction effect for Type D personality by time, indicating that personality did not moderate the effects of cardiac rehabilitation on health status but exerted a stable effect on health status over time.…”
Section: Discussionsupporting
confidence: 91%
“…Preliminary evidence indicates that hostile patients may experience more benefits from cardiac rehabilitation in terms of reductions in anxiety and improvement in quality of life [10]. Type D personality is an emerging risk factor in cardiovascular disease that has been shown to predict adverse health outcomes in CAD [11,12], peripheral arterial disease [13], chronic heart failure [14], patients with life-threatening arrhythmias [15], and patients treated with revascularization procedures [16]. Type D is defined by the two normal and stable personality traits Negative Affectivity [17] and Social Inhibition [18].…”
mentioning
confidence: 99%
“…Thus, our study and data from literature sources [4][5][8][9][10][11] show that the increase of post-operative complications, the severity of pain syndrome, prolongation of hospitalization, and rehabilitation period occur in patients after extensive thoracotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Literary sources indicate that after sternotomy and cardiac surgeries the mediastinitis occurs during the post-operative period in 3% of cases; the pyoinflammatory complications are observed in 20% of patients [4][5][8][9][10][11]. The risk factors for the development of pyoinflammatory complications are repeated surgeries, females, obesity, diabetes mellitus, multifocal atherosclerosis, coronary artery bypass grafting, infective endocarditis, post-operative pneumonia, and urinary tract infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation